Fatal artifacts - Stover, Sharee (Berne, Indiana Annie's, 2023)
Dive into a compelling love story filled with riveting intrigue. In this series, you'll find captivating, intelligent women caught in jeopardy, and the brave steadfast heroes who will stop at nothing to win their hearts as they race against the clock to solve mysteries. Sweet romance joins in fast paced suspense for an edge-of-your-seat read in each book of the Annie's Hearts in Peril series.
113501
Keywords: Romance fiction; Novels